Composing in the scanner: A functional magnetic resonance imaging single case study on visual and auditory imagery. Issue 5 (14th February 2022) - Izadifar, Morteza; Yang, Taoxi; Paolini, Marco; Formuli, Arusu; Bao, Yan
Abstract: "Seeing with the mind's eye" and "hearing with the mind's ear" are two common indicators of musical imagery, and they can be referred to as "visual" and "auditory" musical imagery. However, a question remains open, that is, whether visual and auditory imagery of the same musical composition share the same neural mechanisms. Moreover, how can neural mechanisms guarantee the temporal flow of "musical imagery"? To answer these questions, we report here a preliminary single case study using functional magnetic resonance imaging with an eminent composer who imagined one of his compositions in two states of mind as compared to his resting‐state activity. In the visual imagery condition, he imagined visually the score of his composition in a continuous way. In the auditory imagery condition, he imagined auditorily the same musical composition with pauses. In spite of the modality and temporal differences, the two types of mental imagery showed similar temporal durations for the same musical composition. However, different patterns of neural activation were observed for visual and auditory imagery with one important exception, that is, a common activation pattern was observed in the left medial temporal gyrus in both visual and auditory imagery. We speculate that the left medial temporal gyrus may play an important role in the creation of apparent temporal continuity in musical imagery and perhaps even in conscious information processing in general.